Convergence and Media Repositioning (An Analysis of Information Dissemination Strategies on the Instagram Account @tvOneNews) - Suwadi Suwadi; Amin Aminudin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The transformation of the communication landscape in the digital era has compelled conventional mass media to adapt and evolve in order to remain relevant amid the shifting patterns of public information consumption. This study aims to analyze the information dissemination strategies employed by tvOne through its Instagram account @tvOneNews as a manifestation of media convergence. The study adopts a qualitative descriptive approach, utilizing content analysis and digital observation methods, focusing on the forms of content, patterns of news presentation, and the interactions between the media and its audiences on the Instagram platform. The theoretical foundation of this research is based on Henry Jenkins’ (2006) Media Convergence Theory, which explains the process through which various media platforms merge and interact, blurring the boundaries between traditional media (television) and new media (social media). Convergence is understood not merely as a technological integration but also as a cultural transformation and a shift in user participation patterns in producing and consuming information. The findings reveal that @tvOneNews has repositioned itself from a one-way broadcasting medium to a participatory media platform, emphasizing speed, visual storytelling, and interactivity. This convergence strategy enables tvOne to expand audience reach, enhance engagement, and strengthen its institutional image within the digital sphere. Thus, the practice of media convergence in @tvOneNews represents a concrete example of the transformation of television journalism toward a more collaborative and adaptive communication ecosystem.